Domestic service and motherhood in the files of minors: new questions and historiographical perspectives (Buenos Aires, 1940-1950) - Perez, Inés (Facultad de Humanidades y Ciencias de la Educación. Universidad Nacional de La Plata, 2019)
This article shows that the files of minors opened by the Sociedad de Beneficencia de la Capital offer relevant material to address domestic workers' experiences of maternity in the middle decades of the 20th century Buenos Aires. In particular, it is argued that this source not only allows the analysis of the circumstances in which those experiences took place, but also the workers' agency, their capacity to develop care strategies for their children and, even more, to have an impact in their trajectories within the minority system.